2004
DOI: 10.1158/1078-0432.ccr-04-1187
|View full text |Cite
|
Sign up to set email alerts
|

Administration of CI-1033, an Irreversible Pan-erbB Tyrosine Kinase Inhibitor, Is Feasible on a 7-Day On, 7-Day Off Schedule

Abstract: Purpose: To determine the maximum tolerated dose of administrating CI-1033, an oral 4-anilinoquinazoline that irreversibly inhibits the tyrosine kinase domain of all erbB subfamilies, on an intermittent schedule, and assess the interaction of CI-1033 with food on the pharmacokinetic behavior.Experimental Design: Escalating doses of CI-1033 from a dose level of 300 mg/day for 7 days every other week were administered to patients with advanced solid malignancies. Plasma concentration-time data sets from all eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…In the current study, skin rash was noted in 50% of patients, although the majority of rashes were mild (grade 1), with no grade 3 or 4 rash noted. Grade 3 skin rash has been reported as a treatment-related event in other studies using doses of CI-1033 of z250 mg/d (20,21).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the current study, skin rash was noted in 50% of patients, although the majority of rashes were mild (grade 1), with no grade 3 or 4 rash noted. Grade 3 skin rash has been reported as a treatment-related event in other studies using doses of CI-1033 of z250 mg/d (20,21).…”
Section: Discussionmentioning
confidence: 85%
“…However, it is unlikely that CI-1033 alone contributed to the high incidence of neutropenia seen in this trial as no leukopenia, neutropenia, or febrile neutropenia has been reported in preclinical and phase I studies of single-agent CI-1033 (13,20) nor in trials using the EGFR TKIs gefitinib and erlotinib (31 -34) and lapatinib, a dual erbB-1/erbB-2 TKI (35).…”
Section: Discussionmentioning
confidence: 89%
“…This result is consistent with the clinical efficacy of the compound (Pharmaprojects database, www.pjbpubs.com͞pharmaprojects͞index.htm), but the direct interaction has not been demonstrated to our knowledge. Finally, we find that EKB-569 and CI-1033, EGFR inhibitors that have completed phase I clinical trials (26,27) Abbreviations: EGFR, EGF receptor; GIST, gastrointestinal stromal tumor. database), potently inhibit the erlotinib-and gefitinib-resistant EGFR(L858R͞T790M) variant.…”
mentioning
confidence: 94%
“…Increased erbB expression was shown to be a negative prognostic factor (3,4) in non-small cell lung cancer (NSCLC; ref. 5), breast (6,7), prostate (8,9), head and neck (10), brain (11), ovary (12,13), and stomach cancers (14,15), providing the rationale for development of compounds inhibiting erbB signaling (7).…”
mentioning
confidence: 99%